Analisis Sistem Produksi, Produktivitas, dan Pendapatan Usaha Tani Benih Kentang G0 - G1 Berdasarkan Teknologi Konvensional dan Smart Farming - Hasanudin, Raden Fabian Mochamad; Noor, Trisna Insan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
CV Bumi Agro Technology is a company that has been established since 2011 with a focus on potato and vegetable breeding. The potato plant (Solanum tuberosum L.) is a tuber plant that is rich in carbohydrates and can be used as a substitute for staple foods with very profitable potential. The problem with potatoes in West Java now is that the amount of productivity and production is decreasing, currently, the implementation of Smart Farming can be one of the systems implemented to utilize production inputs effectively and increase productivity by comparing the conventional production system with that of CV Bumi Agrotechnology which uses smart farming. This research aims to find out the application of Smart Farming by looking at the productivity and production of G0 potato seeds at CV Bumi Agro Technology and to find out the comparison of productivity, farming income, and the G0 potato seed production system with the application of Smart Farming and conventional at CV Bumi Agro Technology. This research is qualitative research with descriptive analysis. The results of this research show an increase in the amount of production and productivity which is supported by the assistance of Smart Farming by looking at the calculation of farming income analysis, namely R/C with a result of 1.54 which can be said to mean that the company makes a profit, while conventional farmers have a result of 1.33.